Factors that shape recurrent miscarriage care experiences: findings from a national survey - Caragh Flannery; Marita Hennessy; Rebecca Dennehy; Karen Matvienko-Sikar; Con Lucey; Jennifer Ui Dhubhgain; Keelin O’Donoghue (BMC Health Services Research, 2023)
Abstract Background Learning what matters to women/couples with recurrent miscarriage (RM) is essential to inform service improvement efforts and future RM care practices. Previous national and international surveys have examined inpatient stays, maternity care, and care experiences around pregnancy loss, but there is little focus on RM care. We aimed to explore the experiences of women and men who have received RM care and identify patient-centred care items linked to overall RM care experience. Methods Between September and November 2021, we invited people who had experienced two or more consecutive first trimester miscarriages and received care for RM in Ireland in the ten-year period prior to participate in a cross-sectional web-based national survey. The survey was purposefully designed and administered via Qualtrics. It included questions on sociodemographics, pregnancy and pregnancy loss history, investigation and treatment for RM, overall RM care experience, and patient-centred care items at various stages of the RM care pathway such as respect for patients' preferences, information and support, the environment, and involvement of partners/family. We analysed data using Stata. Results We included 139 participants (97% women, n = 135) in our analysis. Of the 135 women, 79% were aged 35–44 years (n = 106), 24% rated their overall RM care experience as poor (n = 32), 36% said the care they received was much worse than expected (n = 48), and 60% stated health care professionals in different places did not work well together (n = 81). Women were more likely to rate a good care experience if they had a healthcare professional to talk to about their worries/fears for RM investigations (RRR 6.11 [95% CI: 1.41–26.41]), received a treatment plan (n = 70) (RRR 3.71 [95% CI: 1.28–10.71]), and received answers they could understand in a subsequent pregnancy (n = 97) (RRR 8 [95% CI: 0.95–67.13]). Conclusions While overall experience of RM care was poor, we identified areas that could potentially improve people’s RM care experiences – which have international relevance – such as information provision, supportive care, communication between healthcare professionals and people with RM, and care coordination between healthcare professionals across care settings.